Effectiveness of SunPlus as an Accounting Information System in SDAC East Indonesia Union Conference Using DeLone & Mclean Information System Success Model - Roy Mandagi; Raymond Manopo; Elvis Ronald Sumanti (CogITo Smart Journal, 2024)
Faith-based organizations play a pivotal role in society, necessitating robust information management systems for efficient functioning. This study examines the effectiveness of SunPlus, an accounting information system, within the context of the Seventh-day Adventist Church (SDAC), utilizing the Delone & McLean information system success model. The SDAC is a global faith-based organization overseeing numerous institutions. Data for this study was gathered through a questionnaire distributed among all SunPlus users within the SDAC East Indonesian Union Conference, which yielded responses from 80 participants. The findings highlight the significant impact of information and system quality on user usage and satisfaction, which in turn affect the overall net benefit to the organization. However, the study also reveals that service quality variables do not significantly influence usage and user satisfaction. Consequently, while SunPlus serves as an essential accounting information system, it may require additional enhancements to achieve optimal effectiveness in meeting the organization's needs. The study underscores the importance of continuous evaluation and improvement of information systems in faith-based organizations to ensure they adequately support their complex administrative and operational functions. These findings are crucial for the SDAC and similar organizations striving to enhance their information management systems for better performance and user satisfaction.